Inconsistent Growth Response to Fertilization and Thinning of Lodgepole Pine in the Rocky Mountain Foothills Is Linked to Site Index - Bradley D. Pinno; Victor J. Lieffers; Simon M. Landhäusser (International Journal of Forestry Research)
Fertilization of conifers often results in highly variable growth responses across sites which are difficult to predict. The goal of this study was to predict the growth response of lodgepole pine (Pinus contorta var. latifolia) crop trees to thinning and fertilization using basic site and foliar characteristics. Fifteen harvest-origin stands along the foothills of the Rocky Mountains of Alberta were subjected to six treatments including two levels of thinning (thinning to 2500 stems per hectare and a control) and three types of fertilization (nitrogen-only fertilization, complete fertilization including nitrogen with added P, K, S, Mg, and B, and no fertilization). After three growing seasons, the growth response and foliar status of the crop trees were examined and this response was related to site and foliar characteristics. There was a small and highly variable additive response to fertilization and thinning; diameter growth of crop trees increased relative to the controls an average of 0.3 cm with thinning, 0.3 cm with either N-only or complete fertilization and 0.6 cm when thinned and fertilized. The increase in diameter growth with thinning and nitrogen-only fertilization was positively related to site index but not to any other site factors or pretreatment foliar variables such as nutrient concentrations, ratios, or thresholds.